Financial Feasibility Of The Vaname Shrimp Farming Business In The Purworejo Regency - Putri Makalingga; Any Suryantini; Lestari Rahayu Waluyati (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2018)
The study concerned here was aimed at determining the financial feasibility of vaname shrimp farming business in the Purworejo Regency. It used a descriptive method of analysis. The data analyzed were primary and secondary data. The research site was determined purposively (i.e., via purposive sampling) in the Purworejo District by considering the vaname shrimp cultivation there. The analysis used the financial feasibility analysis, Net Present Value (NPV), Internal Rate of Return (IRR), and Net Benefit/Cost Ratio (Net B/C Ratio). The result concerning financial feasibility was obtained from the earnings of vaname shrimp farming business amounting to 1,415,992,500 IDR (Rp 1,415,992,500, with IDR or Rp referring to Indonesian rupiah as USD is to US dollar) with the total cost incurred in one year of production estimated to be 364,207,148 IDR, a revenue of 1,051,785,352 IDR, a profit of 999,196,084 IDR, an NPV (NPV>1 as criterion) of 2,539,407,216 IDR, an IRR (IRR>interest rate of 7.6% as criterion) of 98%, and a Net B/C Ratio (net B/C ratio>1 as criterion) of 2.01. Thus, from the results of the financial feasibility analysis, it could be concluded that the business of vaname shrimp farming in the Purworejo Regency is feasible to run. Based on the research concerned here, the suggestions that could be given concerning the activities of shrimp farming business are workforce training and guidance are given to improve the competitiveness of the farmers. Farmers must know about how to cultivate good fish with the quality of fishery products and becoming responsible farmers.